Navigating Digital Transformation Strategies for Sustaining Competitive Advantage in the AI Era - Najem, Nora Rashid; Salman, Muhanad Kadhum; Mohammed, Moroj; Madhi, Zainab Jali (Journal of Ecohumanism, 2024)
Background: Digital transformation has emerged as a critical strategy for firms seeking to maintain and improve their competitive advantage in the quickly growing AI era. Incorporating AI technologies creates both potential and problems, and a thorough grasp of successful digital transformation initiatives is needed. Objective: The article aims to investigate and explain the tactics that firms may use to successfully manage digital transformation and maintain their competitive advantage in the AI-driven market landscape. Methods: The study takes a mixed-methods approach, combining qualitative analysis of case studies from top firms that have successfully incorporated AI technologies with quantitative data from industry reports and surveys. This dual approach ensures a comprehensive understanding of strategic theories and activities. Results: The findings show that firms prioritizing a clear vision, investing in continuous learning and skill development, and cultivating an innovative culture are more likely to succeed in their digital transformation initiatives. Furthermore, the report emphasizes the relevance of agile approaches and robust data governance in gaining a sustainable competitive edge. Conclusion: The study indicates that while AI integration is critical for digital transformation, the success of such programs is strongly dependent on strategic planning, organizational culture, and ongoing adaptability to technological advances. These insights are helpful for firms looking to negotiate the complexity of digital transformation and preserve a competitive advantage in the AI era.